Aptamers provide superior stainings of cellular receptors studied under super-resolution microscopy - Gomes de Castro, Maria Angela; Höbartner, Claudia; Opazo, Felipe (PLOS ONE, 2017)
Continuous improvements in imaging techniques are challenging biologists to search for more accurate methods to label cellular elements. This is particularly relevant for diffraction-unlimited fluorescence imaging, where the perceived resolution is affected by the size of the affinity probes. This is evident when antibodies, which are 10–15 nm in size, are used. Previously it has been suggested that RNA aptamers ( 3 nm) can be used to detect cellular proteins under super-resolution imaging. However, a direct comparison between several aptamers and antibodies is needed, to clearly show the advantages and/or disadvantages of the different probes. Here we have conducted such a comparative study, by testing several aptamers and antibodies using stimulated emission depletion microscopy (STED). We have targeted three membrane receptors, EGFR, ErbB2 and Epha2, which are relevant to human health, and recycle between plasma membrane and intracellular organelles. Our results suggest that the aptamers can reveal more epitopes than most antibodies, thus providing a denser labeling of the stained structures. Moreover, this improves the overall quality of the information that can be extracted from the images. We conclude that aptamers could become useful fluorescent labeling tools for light microscopy and super-resolution imaging, and that their development for novel targets is imperative.